EFFECTS OF GLUCAGON WITH OR WITHOUT INSULIN ADMINISTRATION ON LIVER-GLYCOGEN METABOLISM - (:unkn) unknown (AMER PHYSIOLOGICAL SOC, 1995)
Rats fed ad libitum were given insulin alone (4 U/kg), glucagon alone (25 mu g/kg), or insulin and glucagon sequentially. Phosphorylase a and synthase R activities, hepatic glycogen, uridine diphosphoglu cose, inorganic phosphate (P-i), and plasma glucose, lactate, glucagon, and insulin concentrations were determined over the subsequent 40 min. In separate animals, muscle extraction of 2-deoxy-D-[H-3]glucose also was determined. After glucagon administration, glycogen phosphorylase a and plasma glucose were increased within 5 min. However, the glycogen concentration did not decrease for 20 min. Glucagon administration to rats pretreated with insulin stimulated a similar increase in phosphorylase a activity. Again, glycogen was not degraded for 20 min. After insulin only, glycogen concentration remained unchanged. Plasma glucose decreased as expected. In each group, muscle extraction of 2-deoxy-D-[H-3]glucose increased compared with the controls (P < 0.05). In summary, glucagon and/or insulin administration did not stimulate significant glycogen degradation for 20 min, even though phosphorylase was activated. The mechanism remains to be determined.
Keywords: GLYCOGENOLYSIS; GLYCOGEN PHOSPHORYLASE; PHOSPHORYLASE A ACTIVITY; PHOSPHORYLASE REGULATION; HEPATIC GLYCOGEN; RAT-LIVER; INTRAVENOUS GLUCOSE; CYCLIC-AMP; ADENOSINE; ASSAY; GLUCONEOGENESIS; SENSITIVITY; EPINEPHRINE; INVIVO